Service-based off-grid solar for productive use in poor urban settings: insights from an informal settlement in Cape Town, South Africa - Penlope Yaguma; Federico Caprotti; Priti Parikh (Environmental Research: Energy)
The productive use of energy (PUE) is a critical pathway to development, as it enhances productivity and facilitates income-generating activities. However, PUE is little understood in low-resource urban settings in the context of off-grid energy. Drawing on two projects implemented between 2019 and 2022, this paper presents a case of off-grid solar for PUE in a young, unelectrified informal settlement in Cape Town, South Africa. The projects investigated the state of energy access in the settlement using household surveys and interviews, and installed solar microgrids in partnership with a local off-grid solar provider who deployed a ‘service-based’ provision model. We find that limited energy options in the settlement commensurately limited energy usage mainly to domestic applications. The microgrids provided reliable refrigeration and lighting for small businesses which improved their operations, delivered energy autonomy, and stimulated aspirations for growth. Energy consumption from the microgrids revealed seasonal and temporal variations which requires flexible demand-responsive energy systems, and holds implications for sizing, storage, and scaling. Although targeted, the ‘service-based’ model limited productive uses to only those that fit within the remit of the model and high costs particularly for appliances prohibited wider PUE adoption. These challenges impact the scalability of off-grid solar in informal settlements which calls for innovative financing approaches and increased policy support for off-grid providers operating in these communities. Off-grid solar has the potential to stimulate PUE and alleviate energy poverty in informal settlements, but more case studies are required to widen the evidence-base, thereby advancing South Africa’s energy transitions agenda.